Strategi Pemberian Kepuasan Pelanggan Melalui Peningkatan Kualitas Pelayanan Tamu Hotel Bumi Wiyata Depok - Wati, Sri Harjuna; Addin, Syahrial (www.bsi.ac.id, 2022)
After the revival of the business world from paralysis due to COVID-19, mobility has returned to enliven the business world and competition is getting tougher, including the hotel industry. The purpose of this study is to examine the strategies that can be carried out by the hospitality industry to be able to retain its customers by providing customer satisfaction by improving the quality of guest services, especially Hotel Bumi Wiyata Depok. The hypothesis in this study is that Service Quality (X) has a positive effect on Customer Satisfaction (Y). The data used are primary data derived from questionnaire data from respondents, which are 100 guests who have used the services of Hotel Bumi Wiyata Depok. Secondary data in the form of data related to Hotel Bumi Wiyata comes from related parties. Furthermore, the data is processed using a simple linear regression technique using SPSS ver software. 23. With = 5% , the degree of freedom of the test n – 2 = 98 produces a sig value. variable X is 0.000 < 0.05; R value = 0.811 ; R Square = 0.658 ; t = 13,745 and the regression equation Y = 2,210 + 0,727 X + e. The SPSS output results lead to the conclusion that H0 is rejected H1 is accepted which means that the Quality of Guest Service has a positive effect on Customer Satisfaction at the Bumi Wiyata Hotel Depok